Intentions to use and recommend to others: an empirical study of online banking practices in Portugal and Austria - Loureiro, S. M. C.; Kaufmann, H. R.; Rabino, S. (Online Information Review, 2014)
Purpose - In an online banking context this study seeks to explore the relation between the relationship marketing factors of customer intentions to continue to use services and to recommend these services to others, and the technology acceptance factors of self-control, usefulness, customer value, technology-based service encounter satisfaction and reputation. Innovatively this study also compares the proposed model in two countries, Portugal and Austria. Design/methodology/approach - Derived from a review of previous literature, a survey was developed and data were collected using the online survey service of universities in two countries, Portugal and Austria. The partial least squares approach was employed to test the hypotheses. Findings - The findings showed that self-control and usefulness are important antecedents of customer value delivery. Furthermore perceptions of online bank reputation were enhanced by the satisfaction derived from positive customer encounters with online banking services. Unlike the Portuguese, Austrians' perceptions of bank reputation did not significantly influence their intention to continue to use or their propensity to recommend online banking to others. Originality/value - Based on literature which suggests that constructs such as customer value, trust, satisfaction and reputation are inter-related to the technology acceptance model, this paper extends earlier theoretical frameworks and is the first study to incorporate relationship marketing constructs into a model examining intention to use, and recommending online banking services. The study also differentiates the model in two countries that represent different business and cultural settings: Portugal and Austria.